2016
DOI: 10.1111/are.13091
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a dietary protease‐complex on performance, digestive and immune enzyme activity, and disease resistance of Litopenaeus vannamei fed high plant protein diets

Abstract: The effects of a dietary protease‐complex on growth performance, body composition, digestive and immune enzyme activity of Litopenaeus vannamei and its resistance to a pathogenic Vibrio parahaemolyticus were assessed in a 9‐week trial. A high fish meal diet (HF) containing 200 g kg−1 fish meal and a low fish meal diet (LF) containing 100 g kg−1 fish meal were designed as a positive and negative control respectively. Three other diets (LF+125P, LF+150P, and LF+175P) were manufactured by supplementing graded lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 57 publications
(79 reference statements)
2
45
0
Order By: Relevance
“…The studies in fishes showed that dietary protease significantly increased protease activities in stomach and intestine (Song, ; Zhang, Li, Leng, Han, & Zhang, ), enhanced nutrient digestibility (Chen et al., ; Drew, Racz, Gauthier, & Thiessen, ) and improved the histological structure of digestive tract (Wu, ; Zhang et al., ). The positive effects of exogenous protease on growth performance were also reported in rainbow trout (Zhang et al., ), black carp ( Mylopharyngodon piceus ) (Chen et al., ), crucian carp (Shi, Li, Chowdhury, Chen, & Leng, ), tilapia ( Oreochromis niloticus × O. Aureus) (Li, Chai, Liu, Chowdhury, & Leng, ) and Pacific white shrimp (Li et al., ; Song et al., ).…”
Section: Introductionmentioning
confidence: 69%
“…The studies in fishes showed that dietary protease significantly increased protease activities in stomach and intestine (Song, ; Zhang, Li, Leng, Han, & Zhang, ), enhanced nutrient digestibility (Chen et al., ; Drew, Racz, Gauthier, & Thiessen, ) and improved the histological structure of digestive tract (Wu, ; Zhang et al., ). The positive effects of exogenous protease on growth performance were also reported in rainbow trout (Zhang et al., ), black carp ( Mylopharyngodon piceus ) (Chen et al., ), crucian carp (Shi, Li, Chowdhury, Chen, & Leng, ), tilapia ( Oreochromis niloticus × O. Aureus) (Li, Chai, Liu, Chowdhury, & Leng, ) and Pacific white shrimp (Li et al., ; Song et al., ).…”
Section: Introductionmentioning
confidence: 69%
“…It is generally considered that exogenous enzymes may have been active during the feed‐drying process, thus hydrolysing substrates and anti‐nutrition factors in the feed ingredients (Ai et al, ). Moreover, numerous experiments have proved that the addition of exogenous enzyme will not reduce the activity of endogenous enzymes, but can promote it and improve the utilization rate of feed (Hlophe‐Ginindza et al, ; Lin et al, ; Song et al, ; Zhu et al, ). In this study, the feed conversion and feed intake of experimental groups had improved in different levels, which conjectured that the hydrolysates may have attraction to fish, and it was also speculated that fish which had better digestion had a better appetite, thus the feed intake, feed conversion and the growth performance of fish were improved.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the activity of lipase and trypsin in the liver and intestines of the fish in all the experimental groups was significantly increased compared to that in the control group, which was consistent with the results of Lin et al () who supplemented the multienzyme complex in diets, The activity of protease and amylase in the intestine and hepatopancreas of tilapia were observed improving significantly. Furthermore, the addition of 0.5 g/kg EC could significantly improve the digestive enzyme activities of tilapia in the experiment of Hlophe‐Ginindza et al (), and the activity of protease, amylase and lipase in hepatopancreas of Penaeus vannamei were also observed significantly improving by the addition of supplement 175 mg/kg protease in diets (Song et al, ).The improvement of the digestive enzyme activity was also probably due to the substrates and anti‐nutrition factors hydrolysed which makes the diet to digest easily (Ai et al, ). A significant decrease in the activity of amylase in the fish intestine was observed in the EC4 group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been identified that appropriate addition of exogenous enzymes in the feed can supplement the deficiency of endogenous enzymes and improve the growth performance (Drew et al, ). In addition, previous studies have evidenced that dietary cellulase can increase the ether extract content of the body tissue by 100g/kg, and the addition of phytase (500 U/kg) and cellulase (2 g/kg) in the feed can increase the lipid content of the body tissue (Baruah et al, ; Xavier et al, ). To promote immune performance and pathogen resistance (Abo et al, ; Baruah et al, ; Liu et al, , ; Song et al, ; Zheng et al, ). The immune system of fish is affected by a variety of factors, including disease, pollutants, hormones and feed (Doan et al, ).…”
Section: Introductionmentioning
confidence: 99%